2008
DOI: 10.1016/j.jphotobiol.2008.07.011
|View full text |Cite
|
Sign up to set email alerts
|

UVA-induced photo recovery during early zebrafish embryogenesis

Abstract: DNA photorepair has been widely studied in simple aquatic organisms that live in the marine environment, but is less understood in more complex species that live in freshwater. In the present study, we evaluated UVA-induced DNA photo recovery in embryonic stages of zebrafish, Danio rerio, a freshwater model species. Evaluation of UVB exposure and UVA photo recovery of zebrafish embryos revealed different UVB tolerances and capacities for UVA photo recovery at different stages of development. Effective UVA phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
1
6
1
Order By: Relevance
“…While fli-1 transgenic zebrafish are generally a sensitive indicator of vascular abnormalities (Dong et al, 2008), we did not see a robust effect of PFOS on vascular development. The vasculature of the eye was only mildly affected in PFOS exposed animals while the body trunk vasculature was largely normal.…”
Section: Discussioncontrasting
confidence: 83%
“…While fli-1 transgenic zebrafish are generally a sensitive indicator of vascular abnormalities (Dong et al, 2008), we did not see a robust effect of PFOS on vascular development. The vasculature of the eye was only mildly affected in PFOS exposed animals while the body trunk vasculature was largely normal.…”
Section: Discussioncontrasting
confidence: 83%
“…Embryos exposed to UV radiation followed a dose‐dependent relationship, with the number of dead embryos increasing as the UV radiation dose increased. A well‐noticed effect of UV radiation on D. rerio embryos development was the occurrence of tail malformations, also observed in other studies . This specific effect can be linked with the position of the embryos at the time of exposure to the UV radiation light.…”
Section: Discussionsupporting
confidence: 75%
“…Previous work in zebrafish has demonstrated the capacity of UVA to activate a mechanism, the photoenzymatic repair (PER), which repairs the DNA damage caused by UVB exposure (42). The evidence of the mentioned repair system is the initial detection of photolyase enzyme in 3 hpf zebrafish embryos (43). The induction of PER partially compensates for a considerable decrease in tolerance of UVB exposure at this developmental stage (43).…”
Section: Discussionmentioning
confidence: 99%
“…The evidence of the mentioned repair system is the initial detection of photolyase enzyme in 3 hpf zebrafish embryos (43). The induction of PER partially compensates for a considerable decrease in tolerance of UVB exposure at this developmental stage (43). It is suggested that the higher UVB tolerance at the egg stage may be related to other (dark) repair mechanisms as well as possible shielding by the chorion and other maternally derived photoprotective compounds.…”
Section: Discussionmentioning
confidence: 99%